Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Derive a formula for $C_k-C_{k-3}$ in terms of partial quotients $a_k$ and nominal denominators $q_k$.

Recall that



$$\begin{matrix} \begin{align} p_0&=a_0 & q_0&=1\\ p_1&=a_0a_1+1 & q_1&=a_1\\ p_k&=a_kp_{k-1}+p_{k-2} & q_k&=a_kq_{k-1}+q_{k-2} \end{align} \end{matrix}$$

This is what I did:

$$\begin{align} C_k-C_{k-3}&=\frac{p_k}{q_k}-\frac{p_{k-3}}{q_{k-3}}=\frac{p_kq_{k-3}-p_{k-3}q_k}{q_kq_{k-3}}=\frac{(a_kp_{k-1}+p_{k-2})q_{k-3}-p_{k-3}(a_kq_{k-1}+q_{k-2})}{q_kq_{k-3}}\\ &=\frac{a_k(p_{k-1}q_{k-3}-p_{k-3}q_{k-1})+p_{k-2}q_{k-3}-p_{k-3}q_{k-2}}{q_kq_{k-3}}\\ &=\frac{a_k(p_{k-1}q_{k-3}-p_{k-3}q_{k-1})+(-1)^{k-3}}{q_kq_{k-3}} \end{align}$$

This is because of a theorem which states that


I get stuck here: I do not know how to get rid of the $p$'s so that the expression will be in terms of $a$'s and $q$'s alone.

share|cite|improve this question

1 Answer 1

up vote 2 down vote accepted

Notice that you have proved $$p_kq_{k-3}-p_{k-3}q_k=a_k(p_{k-1}q_{k-3}-p_{k-3}q_{k-1})+(-1)^{k-3}$$ So you have replaced $p_k$ and $q_k$ with $p_{k-1}$ and $q_{k-1}$ (and introduced $a_k$, and $(-1)^{k-3}$). Perhaps if you do the process two more times you will get $p_{k-3}q_{k-3}-p_{k-3}q_{k-3}$, and your troubles will be over.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.